Control Synthesis of Nonholonomic Mobile Robots Under Time-Varying Delays and Input Saturation: Experimental Validation - Antonio Gonzalez-Sorribes; Rafael Carbonell; Angel Cuenca; Julian Salt (IEEE Access, 2024)
This paper presents a new control synthesis methodology for nonholonomic mobile robots subjected to time-varying delays and input saturation constraints. The proposed control method is based on smooth static nonlinear functions, leading to a simpler structure than other available control strategies for this class of systems. In addition, the convergence to a certain target position with guaranteed exponential decay rate can be proved for any orientation error. To this end, a nonlinear Lyapunov-Krasovskii functional has specifically been designed to deal with the inherent discontinuity of the kinematics model as well as the presence of time-varying delays. Thus, the control design can efficiently be addressed by means of Linear Matrix Inequalities (LMIs). Finally, the effectiveness of the proposed control design algorithm is validated through simulation and experimentally using a two-wheeled mobile robot.